IDENTIFIKASI DAN PENETAPAN KALIUM IODAT DALAM GARAM DAPUR YANG BEREDAR DI PASAR KOTA BITUNG DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Kapantow, Anggelia Nelisa; Fatimawali, Fatimawali; Yudistira, Adithya (PHARMACON, 2013)
ABSTRACTIodine deficiency disorder can be prevented by consumption of salt which contains iodine into the body. Based on Indonesian National Standard (SNI), concentration of Potassium iodide(KIO3) were 30-80 ppm. The objectives of this research were to identify and determineconcentration of potassium iodide in salt which marketed in Bitung region. Samples were 9branded salts and 1 sample unbranded. Identification was done by Potassium cation test andIodide anion test. Determination of Potassium iodide were done using spectrophotometerUV-Vis. The results shows that 9 samples contains Potassium iodide (Branded salts), and 1sample did not contains Potassium iodide (Unbranded salt). Based on spectrophotometeranalysis, there were 5 samples comply SNI of KIO3 (31,6-77,6 ppm), 5 samples did notcomply SNI of KIO3 (2,1-28 ppm).Keywords : Potassium iodide, iodine salt, Spectrophotometry UV-vis, Bitung